Pengaruh Instagram dan Fasilitas terhadap Keputusan Berkunjung pada Objek Wisata Alam Air Terjun Sikulikap Kab. Karo Sumatera Utara - Kevin Lubis; Irwan Musriza Harahap (BUDGETING : Journal of Business, Management and Accounting, 2023)
Sikulikap Waterfall is one of the most popular natural tourist destinations in the 80-90s. However, the lack of attention from the Karo Regency Tourism Office made the Silikap Waterfall slowly fade. At the beginning of 2019 this tourist destination was managed again by Ardian Surbakti S.E and Kristian Ginting S.Hut in collaboration with UPT. Bukit Barisan Tahura. The increase in the number of visiting tourists at Sikulikap Waterfall has increased dramatically from 2020 which amounted to 17,025 tourists, in 2021 there were 46,831 tourists and in 2022 there were 90,342 tourists in natural tourist destinations Sikulikap Waterfall which is a phenomenon in this study. The purpose of this study was to determine the effect of instagram and facilities on visiting decisions at the Sikulikap Waterfall natural tourist destination. The research method used is an associative method with a quantitative approach which includes validity test, reliability test, classical assumption test, hypothesis test (t test, F test, and coefficient of determination analysis test). The data analysis technique used in this study is multiple regression analysis, with a total of 97 respondents. Data collection techniques used are distributing questionnaires, and literature study. The results of this study indicate that instagram and facilities simultaneously have a positive and significant effect on tourists' visiting decisions at the Sikulikap Waterfall natural tourist destination with an f-count value greater than f-table, namely 438.655> 3.09. The instagram variable partially has a positive and significant effect on the decision to visit a natural tourist destination in circular water with the results of t-count (2.255) greater than t-table (1.985). Meanwhile, the facility variable has a positive and significant effect on the decision to visit the Sikulikap Waterfall natural tourist destination with the results of t-count (10.724) greater than t-table (1.985), so the hypothesis is accepted. Keywords: Decision to Visit, Facilities, Instagram.